2011
DOI: 10.1007/s10681-010-0338-1
|View full text |Cite
|
Sign up to set email alerts
|

An intraspecific genetic map of water yam (Dioscorea alata L.) based on AFLP markers and QTL analysis for anthracnose resistance

Abstract: Water yam (Dioscorea alata L.) is the most widely cultivated food yams. Despite its importance, its production is limited by anthracnose disease caused by Colletotrichum gloeosporioides (Penz.). The use of resistant yam varieties is the most reliable approach of management of this disease. The speed and precision of breeding can be improved by the development of genetic linkage maps which would provide the basis for locating and hence manipulating quantitative traits such as anthracnose resistance in breeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 42 publications
6
43
0
1
Order By: Relevance
“…The first genetic map of D. alata was generated by Mignouna et al [35] using AFLP markers in an intra-specific F1 cross between TDa 95/00328 as female parent and TDa 87/01091 as male parent. Later, Petro et al [19] reported the establishment of an intra-specific genetic map of D. alata by crossing two diploid breeding lines, Boutou (female resistant parent) and Pyramide (susceptible male parent) from the Caribbean. The resulting map included 523 polymorphic markers from 26 AFLP primer combinations and covered a total length of 1538 cM including 20 linkage groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first genetic map of D. alata was generated by Mignouna et al [35] using AFLP markers in an intra-specific F1 cross between TDa 95/00328 as female parent and TDa 87/01091 as male parent. Later, Petro et al [19] reported the establishment of an intra-specific genetic map of D. alata by crossing two diploid breeding lines, Boutou (female resistant parent) and Pyramide (susceptible male parent) from the Caribbean. The resulting map included 523 polymorphic markers from 26 AFLP primer combinations and covered a total length of 1538 cM including 20 linkage groups.…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular techniques, such as the candidate gene approach to dissect the underlying gene (s) for the trait of interest, would accelerate efforts in introgressing disease resistance into preferred genetic background. Some earlier work investigating the genetic inheritance of anthracnose disease in water yam showed that resistance is likely to be dominant and quantitatively inherited [15, 19]. Mignouna et al [20] used AFLP markers to demonstrate that there is a single major dominant locus, designated as Dcg -1, controlling resistance in the breeding line, TDa 95/00328 and this resistance is isolate specific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To deal with the high level of genetic diversity of C. gloeosporioides in yams (Abang et al, 2003), the use of sustainable resistant yam varieties is the most reliable approach for disease management. The availability of molecular markers linked to the QTLs of anthracnose resistance will facilitate marker assisted selection in breeding programs (Petro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Whenever damages are limited, symptoms may be mistaken with those of the second most frequent pathogens on yams in the Caribbean eCurvularia species, but the latter never sustain epidemics resulting in complete crop wipeout. The disease is mostly found on D. alata, whose varieties demonstrate diverse resistance levels (Petro et al, 2011;Onyeka et al, 2006). Some cultural practices, such as removal of plant residues after harvest, mixed cropping, pruning or weeding out are known to decrease epidemics by Colletotrichum (Chowdhury and Rahim, 2009;Ripoche et al, 2008;Bedimo et al, 2007), while the traditional plantation distance generally falls within infectious dispersal range once these pathogens colonize fields (Penet et al, 2014).…”
Section: Introductionmentioning
confidence: 99%